The end of early music : a period performer's history of music for the twenty-first century - Haynes, Bruce, 1942-2011 (Oxford University Press, 2007)
Covering historical performance practice in its broadest sense this text identifies common performing styles, comparing and using sound recordings from the past. To help musicians distinguish between Period and Romantic styles, it engages with controversial topics in the field in defining the differences between them.